2020
DOI: 10.1021/acsabm.0c00363
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceria-Based Phospholipase-Mimetic Cell Membrane Disruptive Antibiofilm Agents

Abstract: Table of Contents Chemicals and Methods S3 Characterisation of nanoparticles S4 POPG hydrolysis by MALDI-Mass Analysis S7 Phosphatidylcholine hydrolysis UV-Vis assay scheme S8 UV-Visible analysis of p-Nitrophenylphosphatidyl choline (NPPC) hydrolysis S9 Kinetic parameters of NPPC hydrolysis S10 31 P NMR analysis of NPPC hydrolysis S11 XPS and HRTEM analysis of nanoparticles S12 Phosphatidylcholine hydrolysis by nanoceria S13 Confocal study of bacterial cell membrane disruption S13 CFU analysis of Salmonella gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
(101 reference statements)
0
25
1
Order By: Relevance
“…Khulbe et al focused their attention on the phospholipase-like (phospholipase C) mimetic activity of polymer-coated CeO 2 nanoparticles. 16 CeO 2 nanoparticles demonstrated bactericidal activity, causing membrane disruption in a wide range of pathogens, including respiratory pathogens ( Klebsiella pneumoniae ) and biofilm-forming bacteria. 16 Important data on the molecular mechanisms of CeO 2 nanoparticles' interaction with the cell membrane model were obtained by Liu et al , 53 who showed that the interaction of CeO 2 nanoparticles with phosphocholine liposomes composed of two different types of phospholipid, DOPC and DPPC, proceeds mainly via the phosphate groups in the phospholipids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Khulbe et al focused their attention on the phospholipase-like (phospholipase C) mimetic activity of polymer-coated CeO 2 nanoparticles. 16 CeO 2 nanoparticles demonstrated bactericidal activity, causing membrane disruption in a wide range of pathogens, including respiratory pathogens ( Klebsiella pneumoniae ) and biofilm-forming bacteria. 16 Important data on the molecular mechanisms of CeO 2 nanoparticles' interaction with the cell membrane model were obtained by Liu et al , 53 who showed that the interaction of CeO 2 nanoparticles with phosphocholine liposomes composed of two different types of phospholipid, DOPC and DPPC, proceeds mainly via the phosphate groups in the phospholipids.…”
Section: Resultsmentioning
confidence: 99%
“…16 CeO 2 nanoparticles demonstrated bactericidal activity, causing membrane disruption in a wide range of pathogens, including respiratory pathogens (Klebsiella pneumoniae) and biolm-forming bacteria. 16 Important data on the molecular mechanisms of CeO 2 nanoparticles' interaction with the cell membrane model were obtained by Liu et al, 53 who showed that the interaction of CeO 2 nanoparticles with phosphocholine liposomes composed of two different types of phospholipid, DOPC and DPPC, proceeds mainly via the phosphate groups in the phospholipids. 53 The present study demonstrates that citrate-stabilised CeO 2 sol exhibits prooxidant activity towards organic hydroperoxides that were different in nature.…”
Section: Phospholipoperoxidase-like Activity Of Ceo 2 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials mimic natural enzymes in action and not only display pro- or antioxidative catalytic activity but also mimic hydrolase-like activity ( Jiang et al,2019 ). For instance, nanomaterials exhibiting DNAse ( Chen et al, 2016 ) and phospholipase activity ( Khulbe et al, 2020 ) cause hydrolytic cleavage of extracellular DNA (eDNA) and phospholipids, respectively, and display antibiofilm activity. Hence, a brief understanding of the mechanism of different enzyme mimetic actions of nanozymes becomes important toward designing novel nanomaterials.…”
Section: Catalytic Activity Of Nanozymes In Therapeuticsmentioning
confidence: 99%
“…A major component of the bacterial cell membrane is phospholipid, which plays a key role in biofilm formation, and its cleavage could disrupt biofilms. Phospholipase-mimetic ceria-based nanozyme could hydrolyze the phospholipids in bacterial cell membranes and bacterial biofilms efficiently ( Khulbe et al, 2020 ). The study also demonstrated the potential of nanozyme in preventing bacterial colonization on the surface of urinary catheters.…”
Section: Catalytic Activity Of Nanozymes In Therapeuticsmentioning
confidence: 99%